Impact of national holidays and weekends on incidence of acute type A aortic dissection repair - Oudin Anna; Bjursten Henrik; Oudin Åström Daniel; Nozohoor Shahab; Ahmad Khalil; Tang Mariann; Bjurbom Markus; Hansson Emma C.; Jeppsson Anders; Moeller Christian H.; Jormalainen Mikko; Juvonen Tatu; et al. (Nature Publishing Group, 2023)
Previous studies have demonstrated that environmental and temporal factors may affect the incidence of acute type A aortic dissection (ATAAD). Here, we aimed to investigate the hypothesis that national holidays and weekends influence the incidence of surgery for ATAAD. For the period 1st of January 2005 until 31st of December 2019, we investigated a hypothesised effect of (country-specific) national holidays and weekends on the frequency of 2995 surgical repairs for ATAAD at 10 Nordic cities included in the Nordic Consortium for Acute Type A Aortic Dissection (NORCAAD) collaboration. Compared to other days, the number of ATAAD repairs were 29% (RR 0.71; 95% CI 0.54-0.94) lower on national holidays and 26% (RR 0.74; 95% CI 0.68-0.82) lower on weekends. As day of week patterns of symptom duration were assessed and the primary analyses were adjusted for period of year, our findings suggest that the reduced surgical incidence on national holidays and weekends does not seem to correspond to seasonal effects or surgery being delayed and performed on regular working days.